Pertanggungjawaban Hukum Pemerintah Terhadap Insiden Siber Kebocoran Data Pribadi - Syahrial, Shafira Meutia; Makarim, Edmon; Mahardika, Zahrashafa Putri; Anggraini, Ayu Galuh (Technology and Economics Law Journal, 2026)
The United Nations declared the internet a global facility. Over the past decade, the urgency of efforts to protect the safety and security of cyberspace has increased exponentially with numerous malicious cyber incidents impacting infrastructure that provides services to the public. The internet is a communication channel related to the lives of many people, so all countries have a role to protect the internet. The preamble to the 1945 Constitution mandates the formation of a government to protect the Indonesian nation. The government is responsible for state administration based on Article 40 of the ITE Law, particularly in the case of cyber incident involving PDNS personal data leak. This study analyzes the regulations regarding the Government's responsibility for maintaining cybersecurity in electronic public services, the Government's legal responsibility for cyber incident of personal data leak, and the public's legal remedies for losses suffered due to PDNS data leak. This study uses a doctrinal research method. The results of this study are able to clarify who the Government is in Article 40 of the ITE Law. The government in Article 40 of the ITE Law includes all agencies that have affairs and duties related to the security of electronic system. The first agency is the Ministry of Communication and Digital Affairs (Kemenkomdigi) related to electronic system governance and security based on the ITE Law, PP PSTE, Perpres SPBE, Perpres SDI, PDP Law, Perpres Percepatan Transformasi Digital, and Permenkomdigi PSE Lingkup Publik. The second agency is the BSSN related to cybersecurity based on Perpres BSSN, Perpres IIV, and Perpres Keamanan Siber. The third agency is the Indonesian National Police (Polri) related to law enforcement based on the Indonesian National Police Law, ITE Law, KUHP, and PDP Law. The fourth agency is the Ministry of Defense related to cyber defense based on the Minister of Defense Regulation on Cyber Defense Guidelines. The fifth agency is the State Intelligence Agency (BIN) related to cyber intelligence based on Perpres BIN. The sixth agency is the Ombudsman related to oversight of the implementation of public services based on the Ombudsman Law.